The Utility of Small Fishes for the Genetic Study of Human Age-Related Disorders - Dohi, Eisuke; Matsui, Hideaki (Frontiers in Genetics, 2022)
Animal models have been used to model human diseases, and among them, small fishes have been highlighted for their usefulness in various ways, such as the low cost of maintenance, ease of genetic modification, small size for easy handling, and strength in imaging studies due to their relative transparency. Recently, the use of turquoise killifish, Nothobranchius furzeri, which is known to exhibit various aging phenotypes in a short period, has attracted attention in research on aging and age-related diseases. However, when using animal models, it is important to keep their genetic background and interspecies differences in mind for translating them into human diseases. In this article, we obtained the gene symbols of protein-coding genes of turquoise killifish, medaka, zebrafish, and humans from NCBI datasets and extracted common shared genes among four species to explore the potential of interspecies translational research and to apply small fish models for human age-related disorders. Common shared protein-coding genes were analyzed with the Reactome Pathway Database to determine the coverage of these genes in each pathway in humans. We applied common shared genes to the Orphanet database to establish a list of human diseases that contain common shared genes among the four species. As examples, the senescence-related pathways and some pathways of human age-related diseases, such as Alzheimer’s disease, Parkinson’s disease, frontotemporal dementia, nonalcoholic fatty liver disease, progeria, hepatocellular carcinoma, and renal cell carcinoma, were extracted from the curated pathway and disease list to discuss the further utility of fish models for human age-related disorders.